A study of caesarean section at full cervical dilatation - Rami, Bijal D.; Kaul, Somika; Sailor, Asha; Jindani, Shahna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean sections performed in the second stage of labour are difficult and have many implications on both mother and baby. This study was conducted to analyse fetal and maternal outcome in case of caesarean section at full cervical dilatation. Methods: This prospective study was conducted at one of tertiary care teaching institute for period of 1st August 2019 to 31st January 2020. It includes all women delivered by caesarean section at full cervical dilatation at study institute during study period. Cases were looked for parity, maternal age, gestational age, baby birth weight, indication of cesarean section and associated factors. Results: Out of total 3657 deliveries 1690 were delivered by caesarean section, out of which 65 (3.8%) caesarean sections were conducted at full cervical dilation. The most common indication of caesarean section was deep transverse arrest in 66.15% of cases. The maximum number of cases (69.23%) were seen between the age group of 20 to 25 years. Majority of second stage cesarean section (70.77%) were performed in primi gravida. 80% of caesarean sections at full cervical dilatation were performed after 37 weeks of gestation. 15.38% of patients had anemia, 20% had hypertension, 4.61% had history of previous caesarean section. Baby weight at time of birth was 2.5 to 3.5 kg in 67.70% of cases. 15.38% of patients required blood transfusion. Conclusions: A skilled obstetrician is required to take timely and proper decision in such cases and also to conduct cesarean section at second stage of labour.